Optimizing Radiation Risk Assessment in CT Imaging: Establishing Institutional Diagnostic Reference Levels and Personalized Dose Strategies for Chest, Abdomen, and Pelvis Scans - Zuhal Y. Hamd; Huda I. Almohammed; Elbagir Mansour; Abdoelrahman Hassan A. B.; Awadia Gareeballah (Tomography)
Background: As a diagnostic radiology procedure, computed tomography (CT) contributes to patient radiation exposure; hence, it deserves special consideration. The use of diagnostic reference levels (DRLs) is an efficient way to optimize patient radiation dosage. The computed tomography dose index volume (CTDIv) and the dose-length product (DLP) help to measure DRLs. Methods: A retrospective analysis was conducted on 106 patients (43.9% male, 56.1% female; mean age of 48.18 years) who underwent computed tomography chest, abdomen, and pelvis (CT CAP) scans using a Toshiba Aquilion Prime 160-slice CT scanner. Data included patient demographics, CT parameters (mA, tube rotation time, pitch, slice thickness, and slice count), and dose indices: dose length product (DLP), computed tomography dose index volume (CTDIvol), and effective dose. Cancer risks were calculated based on effective dose, patient demographics, and scan parameters. Results: This study demonstrated that the mean values for DLP, CTDIvol, and effective dose were 1719.64 ± 488.45 mGy·cm, 25.97 ± 6.96 mGy, and 27.5 ± 7.82 mSv, respectively. Cancer risk estimates ranged from 0.048% to 1.58%, with higher risks observed for females, younger patients. Significant correlations were found between dose indices and technical parameters, including pitch, kVp, tube rotation time, and slice thickness (p < 0.005). Conclusions: The mean values for DLP, CTDIvol, and effective dose for abdominopelvic scans were higher than those found in previous studies, with significant correlation of weight on these values. Optimizing CT protocols and establishing DRLs tailored to clinical indications are critical for minimizing radiation exposure and enhancing patient safety.